Awareness and Knowledge of Sexually Transmitted Infections among Secondary School Adolescents in Ado Ekiti, South Western Nigeria. (9th August 2015) - Amu, E. O.; Adegun, P. T.
Abstract : Objective . To determine the awareness and knowledge of sexually transmitted infections among adolescents in Ado, South Western Nigeria. Methods . The study was a descriptive cross-sectional design. Five hundred and fifty adolescents selected from public and private secondary schools in Ado Local Government Area of Ekiti State were recruited using a multistage sampling technique. Results . Four hundred and ninety-nine (92.4%) respondents had heard about sexually transmitted infections before, the three most important sources of information being electronic media (68.7%); teachers (68.1%); and print media (44.9%). Eighty percent of the respondents knew only one STI and the two most commonly mentioned ones were HIV/AIDS (78.0%) and gonorrhea (23.0%). More than 75% of the respondents knew the modes of transmission of STIs while some of them equally had misconceptions. The most important symptoms mentioned were weight loss (77.4%), painful micturition (68.9%), and genital ulcer (54.1%). On the whole, only 6.9% of the respondents had good knowledge of STIs; the rest had fair and poor knowledge. Conclusion . Secondary school adolescents in Ado Local Government Area have only a fair knowledge of sexually transmitted diseases. STI studies should be inculcated into the school curriculum and media publicity/enlightenment campaigns about them should be intensified.